PERANCANGAN SISTEM INFORMASI MONITORING PELAYANAN KARANTINA TUMBUHAN “SiMERAQ” - Merry Agustina; Tri Rizqi Ariantoro (Jurnal Ilmiah Matrik, 2019)
Abstract : Public services in government agencies are starting to change from a direct face-to-face way that the process must be back and forth if there is a shortage of files and take a long time, turning into a service online. In order to improve the satisfaction of public service in government agencies, especially the agricultural quarantine Hall of Class II Cilegon, then the process of application of plant quarantine import, export and domistic can be done online using the system, So that the quarantine submission process can be monitored in realtime. This information system consists of two parts, namely the first part is the front end used by the community in monitoring the process of filing plant quarantine. The second part is the back end used by the file verification Officer, the functional coordinator in delivering the task letter to the field officer, the Laboratory officers provide laboratory verification results, the Treasurer sends Billing payments to the community and head of the hall in monitoring every process of quarantine submission from the community. The back end uses the website.